Brazilian Aquaculture: The view of the Ministry of Agriculture, Livestock and Supply based on the General Registration System for Fisheries and Aquaculture (Research, Society and Development, 2020)
Analysis of the aquaculture scenario from the MAPA database in order to outline the profile of Brazilian aquaculture. The methodology employed works data from SisRGP, statistical analysis and quali-quantitative improvement of the data, the results of which show aquaculture based on fish farming in a tank excavated with semi-intensive and intensive tilapia monoculture, using river water and inconsistent records regarding the licensing of the activity. For long-term planning, it is necessary that directive actions be taken, such as conducting a national aquaculture census, georeferencing and creating a database that concentrates the sector's information.